Strategies and Challenges in Implementing Pesantren-Based Da’wah Education - Mamlu'ah, Anis Wati; May, Lourena Fitri; Purnama, Meira Dwi Indah (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2025)
This study explores the implementation of pesantren-based curriculum in da’wah education at Madrasah Aliyah Mamba’ul Ulum, Jambi City, Indonesia. Positioned at the intersection of formal Islamic schooling and classical pesantren traditions, the curriculum reflects a dynamic integration of national educational standards with Kitab Kuning-based instruction. Employing a qualitative case study approach, the research investigates key aspects of curriculum execution, identifies structural and pedagogical challenges, and analyzes strategic responses adopted by the institution. Findings reveal that da’wah education is embedded within formal instructional hours and reinforced through experiential practices such as student sermons, daily worship routines, and muhadhoroh sessions. Despite facing constraints—particularly among non-residential students lacking pesantren backgrounds, limited Arabic proficiency, and resource shortages—the madrasah implements a tiered strategy comprising monthly, semester-based, and annual programs to cultivate da’wah competencies progressively. The integration of textual and contextual learning, supported by Arabic language development, enhances students’ rhetorical, spiritual, and social capacities. The study concludes that the pesantren curriculum serves not only as a vehicle for religious knowledge transmission but also as a transformative framework for shaping communicative and ethically grounded da’i and da’iyyah. These findings underscore the importance of adaptive, participatory, and experience-based approaches in sustaining relevant and impactful da’wah education within contemporary Islamic schooling. This study offers a model for integrating pesantren traditions with modern educational demands in da’wah education.